2018
DOI: 10.1155/2018/8561675
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rapid Urbanization on Vulnerability of Land System from Complex Networks View: A Methodological Approach

Abstract: Rapid urbanization is responsible for the increased vulnerability of land systems and the loss of many crucial ecosystem services. Land systems are typical complex systems comprised of different land use types which interact with each other and respond to external environment processes (such as urbanization), resulting in dynamics in land systems. This work develops a methodology approach by integrating complex networks and disruptive scenarios and applies it to a case study area (Wuhan City in China) to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…The average shortest path length assesses the stability of land use systems in the complex network model. The equation is expressed as follows [52]:…”
Section: Complex Network Modelmentioning
confidence: 99%
“…The average shortest path length assesses the stability of land use systems in the complex network model. The equation is expressed as follows [52]:…”
Section: Complex Network Modelmentioning
confidence: 99%
“…It is of great significance to understand the spatial expansion trend of urban built-up land for guiding the rational expansion of urban land [46][47][48][49][50][51]. Night light data is a common kind of remote sensing data analyzing the city scale [52][53][54].…”
Section: Urban Built-up Land Expansion Simulationmentioning
confidence: 99%
“…e mechanisms that influence such efficiency are complex and diverse [20]. A number of studies have shown that fiscal expenditure, urban population density [23], transportation infrastructure [9,24,25], and urban industrial composition, and layout [26] have an impact on urban construction land efficiency [27]. However, researchers are yet to reach a consensus in regard to the quantitative measurements and mechanisms of urban construction land use efficiency.…”
Section: Variable Selection and Processingmentioning
confidence: 99%